Framework for Analyzing Community-Based Enterprise (CBE): Literature review of organizational architecture and organizational performance - Soviana Soviana (Justus Liebig University, Institute of Farm and Agribusiness Management, 2013)
Community-based enterprise (CBE) has increasingly been acknowledged as a potential solution for environmental-poverty problems in developing countries. However, the imprecision of how the CBE is defined and the lack of clarity regarding the organization of CBE have posed a challenge of identifying effective way to successfully implement the CBE model. These facts have become the motivation of conducting research in this topic. The aim of this working paper is to present a literature review regarding the possibility of assessing the CBE from the organizational perspective, namely by looking at organizational architecture and performance issues. Four features of organizational architecture are taken into account, i.e. contextual constraints, organizational goals, collection of resources, and architectural design. As for organizational performance, the focus is on measuring the relative growth of the triple-bottom-line and survivability dimensions. Some next steps are also suggested at the end of the paper.
Keywords: 330; community-based enterprise; organizational architecture; organizational performance